Dnmt3a-mediated abnormal DNA methylation is associated with myelination deficits in offspring of advanced maternal age rats - Chunxue Jiang; Xinru Yan; Man Xu; Li Cheng; Li Jiang; Wei Han (Molecular Biology Reports, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Visuotactile multimodal fusion with flexible piezo-triboelectric sensors for high-fidelity piano keystroke dynamics decoding - Liang Shen; Man Li; Tingxuan Chen; Qinhua Hu; Bowen Zhang; Enjie Wang; Ji Luo; Mingjun Zhang; Wenjie Wu; Wei Tao (Chemical Engineering Journal, 2026)

A proximity-allosteric Adapter unlocks Cas12a exponential amplification for versatile homogeneous assay - Feiyu Chen; Man Tang; Zhangling Liu; Wuxian Li; Xingping Hu; Linguo Xiang; Lanxin Jiang; Yanna Ban; Jing Wang; Jia Li; Wei Cheng; Tiantian Yang (Analytica Chimica Acta, 2026)

Differentiation of block-scale carbon budgets and synergistic carbon reduction pathways under functional guidance and spatial constraints: Evidence from Wuxi, China - Hui Guo; Wei Sun; Sen Wang; Man Li (Sustainable Cities and Society, 2026)

Chemical-free closed-loop conversion of nitrate into struvite fertilizer via exsolved high-entropy perovskite electrocatalyst - Li-Hui Yang; Yi-Heng Liu; Si-Hao Lv; Man-Ting Liao; Hui Lin; Wei Li; Cao Yang; An-Qi Wang; Hao-Yi Cheng (Journal of Environmental Chemical Engineering, 2026)

Isolation and functional characterization of goose-derived lactic acid bacteria with growth-promoting and gut health benefits in Sanhua geese - Changsheng Jiang; Wenli Shi; Ji Chen; Weitao Wang; Dandan Fang; Wanji Zhan; Wei Zuo; Chuanyan Che; Ahmed H. Ghonaim; Mengmeng Jin; Qianqian Hu; Keli Yang; et al. (Food Chemistry, 2026)

Targeting the phenolic A-ring unifies the toxicology and remediation of environmental estrogens in aquatic environments - Liu-Feng Yu; Yi-Lin Ye; Jie Zhou; Yu-Han Jin; Yu-Han Sun; Li-Xia Yan; Chen-Man Li; Jia-Yi Chang; Wei-Jie Chen; Feng Liu; Yong-Wei Feng; Xiao-Dong Huang; et al. (Environmental Research, 2026)

Nanomaterials as plant delivery carriers: transport mechanisms and design principles - Ye Li; Yezhuo Zhang; Zhun Zhang; Xi Zhang; Hongyang Wu; Man Zhang; Zhuo Li; Yinglang Wan; Yujie Fu; Wei Dong; Ruili Li; Jinxing Lin (Science China Life Sciences, 2026)

Anchoring MoOx nanodots in N-doped porous carbon via a biomimetic strategy: enhanced supercapacitor performance - Li Li; Shou-Cheng Jiao; Chang-Wang Shao; Yu-Man Li; Long-Yu Zhang; Xing-Shun Cong; Xian-Yong Wei; Dan Mu (Fuel, 2026)

A novel Camellia oil microemulsion significantly enhances the bioaccessibility and antioxidant activity of curcumin: a comparative study with macroemulsion - Jingyi Chen; Jiayi Zou; Yuting Yang; Wei Li; Qihui Shui; Man Tian; Yu Zhou; Xingfa Han; Tao Chen; Lijun Zhou (Food Chemistry, 2026)

Structural characterization of an acetylated glucomannan from Aloe barbadensis and its alleviation of murine colitis via coordinated ECM repair and microbiota-metabolism actions - Xiaofeng Guo; Jianmin Guo; Man Li; Jinzi Chen; Lu Li; Xueli Tong; Haiyang Yin; Weijie Xu; Mengmeng Wang; Xie He; Zhihang Zhong; Wei Yang; et al. (Carbohydrate Polymers, 2026)

Integrative analysis of Huangjing-Gegen compatibility in treating COPD: a network pharmacology, molecular docking, and experimental study - Shaoqing Zhu; Jiaruo Li; Lin Chu; Yunpeng Zhu; Wei Wang; Man Wang; Zhenhua Zhu; Fei Mao; Pengjun Liu; Ying Chu (Natural Product Research, 2026)

Preparation and characterisation of two new malonylated rare ginsenosides by acid hydrolysis and their anti-hepatoma activities - Ya-Qian Lu; Xiao-Man Jin; Fu-Rui Zhang; Mei-Hui Li; Wen-Wen Li; Wei Li; Chun-Su Yuan; Zhi Liu (Natural Product Research, 2026)

Three new naphthoquinone-based meroterpenoids from Streptomyces sp. HBERC-16614 with antibacterial activities - Ya-Ni Zhang; Man-Li Liu; Fang Liu; Zhi-Gang Zhang; Zhao-Yuan Wu; Li-Qiao Shi; Zhong-Yi Wan; Yue-Ying Wang; Fei Zhang; Kai-Mei Wang; Wei Fang (Natural Product Research, 2026)

Sediment-dependent phosphorus transport in dammed rivers: The critical role of pretreatment method - Huali Li; Yanqian Wei; Yanxue Xu; Jianjun Zhou; Man Zhang (Journal of Environmental Management, 2026)

Homothorax regulates BarH1 expression and olfactory perception in Monochamus alternatus hope - Qi-Cheng Li; Sheng-Xin Wu; Mei-Jiao Yang; Pu-Yuan Zhang; Yan-Ling Wei; Man-Qun Wang (Insect Biochemistry and Molecular Biology, 2026)

Long-term aging of oxychar and biochar: structural, adsorptive, and microbial transformations - Cheng Ji; Shutao Wang; Man Zhang; Hang Sun; Qinggang Meng; Kexin Zhao; Yifan Li; Shiming Su; Bing Han; Wei Liu (Fuel, 2026)

PfAgo-guided SERS signal conversion for amplification-free and semi-quantitative detection of Salmonella typhimurium in food and physiological samples - Ruibo Zhao; Jingjing Bai; Qiang Zhang; Jiayi Wei; Fei Deng; Myunghee Kim; Xingjie Li; Shuli Man; Weipan Peng; Long Ma (Journal of Hazardous Materials, 2026)

High-performance electrochemical sensor based on an iron phthalocyanine-tetrathiafulvalene polymer for simultaneous detection of catechol and acetaminophen - Chuangyu Wei; Rui Tao; Yang Wang; Meitong Li; Xinyu Yang; Xinrui Niu; Hongyang Man; Xue Cai (Journal of Environmental Chemical Engineering, 2026)

Global evidence on vitamins in human milk: A 2002–2022 systematic review with a focus on China and implications for maternal diet and infant formula - Yan Yang; Xinggang Ni; Nian Liu; Quanzhang Li; Qi Fang; Ignatius Man-Yau Szeto; Sufang Duan; Teng Wei; Tianyu Rao; Zeyuan Deng; Ting Li; Jing Li (Food Research International, 2026)

Contrasting responses of bacterial-mediated soil organic phosphorus transformations to varying rates of nitrogen addition in a Cunninghamia lanceolata plantation - Xiang Zhang; Qiong Zhao; Li-Man Wei; Lin-Hui Wu; Xiang-Min Fang; Yong-Hong Ma; Fu-Sheng Chen (Applied Soil Ecology, 2026)

Rivers as biogeochemical highways: Decoding phosphorus transfer from catchments to coastal zones with insights from the Yellow River - Yanqian Wei; Huali Li; Yanxue Xu; Man Zhang (Journal of Environmental Management, 2026)

Application of Magnetic-Seismic Geophysical Prospecting Technology in Identifying the Carboniferous Volcanic Rocks in the Chepaizi, West Margin of Junggar Basin - Guo-hua Jiao; Wei-ping Zhang; Jin-ke Zhou; Fu-gang Sun; Hai-tao Yang; Man Li; Zhu-qiang Li (Applied Geophysics, 2026)

Dual-source-driven snowman-shaped PMO@MnO2@C@DMSN-SS31 Janus nanomotors for enhanced deep penetration and restoration of mitochondrial function to modulate the inflammatory microenvironment for cartilage repair - Xiaolei Zhang; Zhihan An; Yichen Zhang; Jinquan Cui; Qiang He; Chuandong Cai; Jianing Liu; Zhentao Man; Wei Li (Chemical Engineering Journal, 2026)

Body size drives male reproductive success through nest competition and paternal care in the toad Leptobrachium boringii - Raziya Abliz; Wei Zhang; Shuang Liu; Rufeng Xiong; Chunhua Huang; Jun Li; Mian Zhao; Zhirong Gu; Man Su; Wei Liu; Hua Wu (Animal Behaviour, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

Reverse temporal spectral signal extraction and deep spectral signal decoupling fusion for detection of SCLB infection process - Guohui Liu; Jinyang Chao; Changle Guo; Lulu An; Yang Liu; Hong Sun; Chunqi Zhang; Mingjia Liu; Zheng Cui; Man Zhang; Minzan Li; Wei Yang (Computers and Electronics in Agriculture, 2026)

Quantifying climate conditions for the formation of bauxites and kaolinites - Xiujuan Bao; Yongyun Hu; Xiang Li; Jiaqi Guo; Shuai Yuan; Mengyu Wei; Zhibo Li; Kai Man; Zihan Yin; Jing Han; Jian Zhang; Qiang Wei; et al. (Global and Planetary Change, 2026)

Molecular dipole engineering enabled TiO2 electron transport layers for stable quantum-dot light-emitting diodes - Hang Liu; Pei-Li Gao; Bo Li; Hui Bao; Yin-Man Song; Meng-Wei Wang; Ting Ding; Jing Jiang; Rui-Feng Zheng; Feng-Jia Fan; Hai-Zheng Zhong; Kar-Wei Ng; et al. (Chemical Engineering Journal, 2026)

Benzo[c]chromene-based light-emitting conjugated polymer for high performance deep-blue PLEDs - Hong Ren; Zhiyang Sun; Xiang An; Qian Wu; Xinyu Du; Xiaoqi Guo; Wenyu Chen; Mengyuan Li; Jiabin Liu; Dunliang He; Ning Sun; Lubing Bai; et al. (Chemical Engineering Journal, 2026)

New focus on ecological risks of pesticides: The effect of pesticides on the development of bacterial antibiotic resistance - Yitong Zhao; Jingchen Wu; Chunfeng Wei; Lu Li; Fudong Liang; Yanli Man; Houpu Zhang; Lingxi Han; Hua Fang; Yongquan Zheng; Chao Ju (Journal of Hazardous Materials, 2026)

Construction of carboxymethyl chitosan/oxidized Astragalus polysaccharide cross-linked gel microspheres in alginate system: Improving the tolerance and functional characteristics of Lactobacillus paracasei - Yilin Sun; Man Zhu; Zimu Li; Xinyan Yang; Wei Zhang; Ling Guo; Yujun Jiang; Yu Zhang (Food Research International, 2026)

Coalescent 2D heterostructure for high-efficient surface-enhanced Raman scattering and electrochemical sensing - Muhammad H. Nawaz; S. Santhoshkumar; Thi H. Ho; Balamurugan Arumugam; Mohamed Gamal Mohamed; Tuan V. Vu; Yousra.M. Nabil; Mohammed G. Kotp; Li-Wei Tu; Hung-Duen Yang; Ahmed F.M. EL-Mahdy; Shiu-Ming Huang; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “Composite inclusion complexes containing hyaluronic acid/chitosan nanosystems for dual responsive enrofloxacin release” [Carbohydrate Polymers 252 (2021) 117162] - Yuda Liu; Dongmei Chen; Aoxue Zhang; Man Xiao; Zhenxia Li; Wanhe Luo; Yuanhu Pan; Wei Qu; Shuyu Xie (Carbohydrate Polymers, 2026)

SREBP2 confers ferroptosis resistance by targeting GPX4 in colorectal cancer - Huage Zhong; Ruiqi Chen; Tianyu Chen; Min Lin; Siqi Wen; Man Zhang; Dejun Liu; Junfeng Yu; Jinchi Chen; Bei Yi; Rong Liang; Wei Jiang; et al. (Apoptosis, 2026)

Co-inoculation of Bacillus amyloliquefaciens and Pleurotus ostreatus alleviates replanting obstacles in continuously cropped soil by enhancing the soil nutrient cycle and beneficial microorganisms - Xue Luo; Man Xu; Xin-Li Yan; Rui Xing; Yi-Jin Kang; Hong-Wei Wang (Rhizosphere, 2025)

OptimDase: An Algorithm for Predicting DNA Binding Sites with Combined Feature Encoding - Zhendong Liu; Jun S. Liu; Dongqing Wei; Rongjun Man; Jiamin Jiang; Bofeng Zhang; Liping Li; Zhiyong Zhao (Interdisciplinary Sciences: Computational Life Sciences, 2025)
Identifying DNA binding sites remains a critical task in bioinformatics, with applications ranging from gene regulation studies to drug design. Although progress has been made in computational techniques, we still face challenges such as data complexity and prediction accuracy. In this paper, we introduce OptimDase, a new algorithm. It integrates feature encoding with optimum decision-making frameworks to improve DNA binding site prediction. OptimDase integrates multi-scale scanning and feature selection strategies, making it highly effective for both classification and regression tasks. Our experiments demonstrate that OptimDase achieves superior performance with an accuracy of 0.8943 in classification tasks and an RMSE of 0.0054 in regression tasks, outperforming existing algorithms in key evaluation metrics. These results highlight OptimDase’s portability and robustness, making it an effective solution for identifying DNA binding sites and advancing the applications of drug design. Graphical Abstract

Post-fire tensile behavior of wire arc additively manufactured duplex stainless steel plates - Zhichao Gong; Hai-Ting Li; Wei Chen; Ou Zhao; Man-Tai Chen (Engineering Structures, 2025)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

Protective effects and mechanisms of Saikosaponin A against myocardial ischemia based on network pharmacology, molecular docking, and experimental validation - Hongyu Wu; Wei Wang; Lintong Wen; Jie Cheng; Yurun Xue; Man Liao; Haoying Li; Xia Li; Jingyi Zhang; Shijiang Sun; Shengjiang Guan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Recent advances in electrospray encapsulation of probiotics: influencing factors, natural polymers and emerging technologies - Haifu Jia; Yuanyuan Li; Yueling Tian; Nan Li; Miao Zheng; Wei Zhang; Yujun Jiang; Qianyu Zhao; Chaoxin Man (Critical Reviews in Food Science and Nutrition, 2025)

Antibiotic resistance genes in multi-matrices of Chaohu Lake: Spatiotemporal variation and correlation with pesticides and PPCPs - Hao Yang; Hongwei Fu; Yutong Zhao; Run Li; Man Cao; Yi Liu; Yachao Ni; Wei Song; Yangyang Liang; Panyuan Cai; Wei Chang; Fangbiao Tao; et al. (Journal of Hazardous Materials, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Immunosuppressive role of benzo[a]pyrene exposure in prostate cancer progression - Zhijin Zhang; Wentao Zhang; Huan Wang; Haotian Chen; Hong Wang; Yang Yu; Danjing Shen; Man Pi; Yang Wu; Ming Luo; Yanyan He; Shiyu Mao; et al. (Journal of Environmental Sciences, 2025)

Enhancing lipid yield in freshwater microalgae through synergistic abiotic stressors for sustainable biodiesel production - Uganeeswary Suparmaniam; Cheng Yaw Li; Man Kee Lam; Nurul Tasnim Sahrin; Hemamalini Rawindran; Chin Seng Liew; Jun Wei Lim; Inn Shi Tan; Sie Yon Lau; Bridgid Lai Fui Chin (Biomass and Bioenergy, 2025)

A new strategy for removing insecticide etoxazole from soil using a combination of a novel Paracoccus versutus Y4 and a fungal mycelium carrier - Man Xu; Xue Luo; Xin-Li Yan; Xiao-Yu Cai; Lin-Lin Wang; Feng Ge; Hong-Wei Wang (Journal of Hazardous Materials, 2025)

Investigation on Thixotropic Properties of Coal by Nanoindentation - Jingjie Guo; Wei Li; Man Wang; Dong Deng; Mengqi Zhou (Rock Mechanics and Rock Engineering, 2025)

Analysis and Control Techniques of Ultra-Shallow Buried Tunnels in Rain-Affected Backfill Soil - Peng-cheng Wang; Li-yang Su; Shu-jie Shang; Xiang-yu Jia; Wei-teng Li; Feng-chuan Jiang; Chun-qing Liu; Xin-jie Man (Geotechnical and Geological Engineering, 2025)

Effects of combination of UV-B irradiation and drying on the physicochemical properties of key components and processing quality of germinated whole wheat flour - Ting Wei; Wentong Liu; Jiahao Huang; Na Ji; Qingjie Sun; Man Li; Meng Ma; Fengwei Xie (Journal of Cereal Science, 2025)

Alveolar surfactant-mimicking inhaled biomimetic nanovaccine with alveolar macrophage-targeting property potentiates anti-mpox immunity - Bin Li; Jiamei Wang; Judun Zheng; Wei Wang; Lingjie He; Yan Yan; Xinting Fu; Xingjie You; Man Gu; Han Duan; Yue Jia; Qin Gu; et al. (Chemical Engineering Journal, 2025)

Retraction notice to “Effect of the defoliant tribufos on the reproductive ability of Japanese quail (Coturnix japonica)” [Chemosphere 352 (2024) 141430] - Xin-Li Yan; Xue Luo; Man Xu; Ying Shi; Yi-Jin Kang; Hong-Wei Wang (Chemosphere, 2025)

Intelligent identification of internal leakage in natural gas pipeline control valves based on Mamba-ARN - Wei Li; Shuxun Li; Jianjun Hou; Jianwei Wang; Man Zhao (Process Safety and Environmental Protection, 2025)

Fabrication of electrically conductive polysulfone loose nanofiltration composite membranes with a dually charged separation layer for efficient separation of dye/salt mixtures: Electric-field-assisted formation of porous support layers - Kang Li; Shuhao Qin; Wei Gao; Mingmi Wu; Man Yang; Chengtao Gao; Shengbao He; Huiju Shao (Journal of Environmental Chemical Engineering, 2025)

Seasonality, worker caste, and the interaction between island area and habitat type influence the thermal tolerance of ants on fragmented habitat islands - Yuhao Zhao; Chenxiao Wu; Chi Man Leong; Jiaxin Li; Wei Lu; Yijuan Xu; Xingfeng Si; Nathan J. Sanders (Marine Life Science & Technology, 2025)

Solasodine binds to glucocorticoid receptor to ameliorate airway remodeling and excessive autophagy in bronchial smooth muscle cells for allergic asthma - Zhen Guo; Jun-li Liu; Yan-ni Fang; Xiao-man Guo; Chun-long Ma; Jing-wei Wang (Toxicology and Applied Pharmacology, 2025)

Analysis of the effect of 60 Co irradiation sterilization on the chemical composition of volatile organic compounds in Rhizoma Acori Tatarinowii using GC-IMS - Man-Shu Zou; Li-Yan Xie; Wei Zhou; Yun Xiang; Chang Lei; Dan Huang (Natural Product Research, 2025)

Effect of sediment on fluvial phosphorus and aquatic water quality - Huali Li; Yanxue Xu; Yanqian Wei; Man Zhang; Jianjun Zhou (Journal of Environmental Management, 2025)

Molecular chelating and shielding operation for organic photoelectrochemical transistor detection of chlorpyrifos - Lang Lin; Yu-Mei Li; Rui Ban; De-Man Han; Feng-Zao Chen; Wei-Wei Zhao (Analytica Chimica Acta, 2025)

Quercetin protects against neuronal toxicity by activating the PI3K/Akt/GSK-3β pathway in vivo models of MPTP-induced Parkinson’s disease - Yajuan Li; Minghao Man; Yiyuan Tian; Gang Zhao; FengZhou Liu; JingYu Zhao; Songya Huang; Junhui Xue; Wei Chang (Inflammopharmacology, 2025)

BarH1 regulates the expression of conserved odorant-binding protein 22 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Ao Liu; Yi Wei; Rui-Lin Zhang; Hazem Abdelnabby; Man-Qun Wang (Insect Biochemistry and Molecular Biology, 2025)

Correction: Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2025)

Diet shift and allometric growth in the early development Odontobutis potamophila - Miao Xiang; Kun Xiao; Hongliang Xu; Bo Li; Hongxi Guo; Zhanhu Yang; Chuankun Zhu; Man Wang; Jie Wang; Wei Xin; Songguang Xie; Xiaoming Zhu; et al. (Aquaculture, 2025)

A comprehensive molecular phylogeny of the genus Sylvirana (Anura: Ranidae) highlights unrecognized diversity, revised classification and historical biogeography - Yun-He Wu; Man-Hao Xu; Chatmongkon Suwannapoom; Sang Ngoc Nguyen; Robert W. Murphy; Theodore J. Papenfuss; Amy Lathrop; Felista Kasyoka Kilunda; Wei Gao; Zhi-Yong Yuan; Jin-Min Chen; Liang Zhang; et al. (Molecular Phylogenetics and Evolution, 2025)

Combined processing technologies: Promising approaches for reducing Allergenicity of food allergens - Lidong Pang; Runze Li; Chen Chen; Zhen Huang; Wei Zhang; Chaoxin Man; Xinyan Yang; Yujun Jiang (Food Chemistry, 2025)

Exosome-anchored scholzite conversion coating on titanium with long-term stability and immunomodulatory ability to enhance osteogenesis - Shimin Dai; Benzhao Huang; Peng Wang; Xiaoqing Lu; Shishuo Li; Zhibo Zhao; Xiao Li; Ningbo Li; Jiahui Yu; Zhentao Man; Wei Li; Bing Liu (Chemical Engineering Journal, 2025)

Combined Effects of Cadmium and Lead on Growth Performance and Kidney Function in Broiler Chicken - Man Zhao; Longqiang Xie; Wenbin Huang; Meiling Li; Xin Gu; Wei Zhang; Jintao Wei; Niya Zhang (Biological Trace Element Research, 2025)

Urban estuary serves as a critical nexus for the land-sea transfer of the terrestrial pathogen Toxoplasma gondii - Xin-Kun Zhu; Hany M. Elsheikha; Tao Yang; Man-Yao Li; Wei Cong (Science of The Total Environment, 2024)

Early postnatal and concurrent exposure to metals and neurobehavioral outcomes at 5 years: Associations with individual environmental exposures and mixtures - Sui-Ling Liao; Shen-Hao Lai; Yuan-Ting Hsu; Li-Chen Chen; Ming-Han Tsai; Man-Chin Hua; Tsung-Chieh Yao; Kuan-Wen Su; Kuo-Wei Yeh; Chih-Yung Chiu; Shau-Ku Huang; Jing-Long Huang (NeuroToxicology, 2024)

Comparative analysis of lipid composition in colostrum and mature milk from women of seven Chinese ethnic groups - Zhiyi Zhang; Teng Wei; Xinggang Ni; Ting Li; Ignatius Man-Yau Szeto; Sufang Duan; Yalu Yan; Wenhui Ye; Jing Li; Zeyuan Deng (International Dairy Journal, 2024)

In-field grading and sorting technology of apples: A state-of-the-art review - Jiangfan Yu; Zhao Zhang; Yifei Li; Wanjia Hua; Xinyu Wei; C. Igathinathane; Mustafa Mhamed; Wenqiang Zhang; Xiaoqiang Jiao; Liling Yang; Man Zhang; Han Li (Computers and Electronics in Agriculture, 2024)

Sexual differentiation and juvenile hermaphroditism in silver pomfrets: Direction, process, and dietary factors - Yaya Li; Mingzhe Yuan; Peng Shi; Keyan Cai; Jiabao Hu; Man Zhang; Youyi Zhang; Yuanbo Li; Mengke Tang; Zukang Feng; Chunlai Qin; Wei Ge; et al. (Aquaculture, 2024)

High-quality litter exerts a greater effect on soil carbon gain in unrestored than restored pine plantations - Shiting Li; Yongmeng Jiang; Maokui Lyu; Cui Deng; Wei Deng; Man Wang; Jueling Liu; Yuming Lu; Jinsheng Xie (Science of The Total Environment, 2024)

Adsorption behavior of heavy metals onto microplastics derived from conventional and biodegradable commercial plastic products - Po-Wen Chen; Man-Ni Hsiao; Li-Wei Xiao; Zhen-Shu Liu (Science of The Total Environment, 2024)

Protective effect of scorpion venom oligopeptides in human umbilical vein endothelial cells under benzo(α)pyrene exposure - Wei Chen; Ruimin Chen; Man Zheng; Daixu Li; Lin Lu (Natural Product Research, 2024)

Spatiotemporal Point–Trace Matching Based on Multi-Dimensional Feature Fuzzy Similarity Model - Yi Liu; Ruijie Wu; Wei Guo; Liang Huang; Kairui Li; Man Zhu; Pieter van Gelder (Journal of Marine Science and Engineering, 2024)
Identifying ships is essential for maritime situational awareness. Automatic identification system (AIS) data and remote sensing (RS) images provide information on ship movement and properties from different perspectives. This study develops an efficient spatiotemporal association approach that combines AIS data and RS images for point–track association. Ship detection and feature extraction from the RS images are performed using deep learning. The detected image characteristics and neighboring AIS data are compared using a multi-dimensional feature similarity model that considers similarities in space, time, course, and attributes. An efficient spatial–temporal association analysis of ships in RS images and AIS data is achieved using the interval type-2 fuzzy system (IT2FS) method. Finally, optical images with different resolutions and AIS records near the waters of Yokosuka Port and Kure are collected to test the proposed model. The results show that compared with the multi-factor fuzzy comprehensive decision-making method, the proposed method can achieve the best performance (F1 scores of 0.7302 and 0.9189, respectively, on GF1 and GF2 images) while maintaining a specific efficiency. This work can realize ship positioning and monitoring based on multi-source data and enhance maritime situational awareness.

Nrf2 deficiency exacerbated pulmonary pyroptosis in maternal hypoxia-induced intrauterine growth restriction offspring mice - Dan Chen; Ling-yun Man; Ying-ying Wang; Wei-ying Zhu; Hui-min Zhao; Sheng-peng Li; Yan-li Zhang; Shuai-chao Li; Ya-xian Wu; Ling-Ai; Qing-feng Pang (Reproductive Toxicology, 2024)

Potentially toxic element source apportionment and risk assessment in agricultural soils around a large-scale Pb-Zn mine in Southwest China - Heng Wei; Xuekui Niu; Minmin Li; Canwen Cui; Zhonghua Wei; Wei Long; Man Tang; Hong Yu; Peng Zhang; Liping He; Bo Pan (Journal of Environmental Chemical Engineering, 2024)

Optically manipulated nitrate-salt-based direct absorption solar collectors for a photothermal energy harvesting system - Chun-Man Kan; Sih-Wei Chang; Jun-Yi Li; Juan Carlos Cisneros; Hsuen-Li Chen (Chemical Engineering Journal, 2024)

Drug evaluation platform based on non-destructive and real-time in situ organoid fate state monitoring by graphene field-effect transistor - Meng Tian; Jinsong Wei; Enguang Lv; Chonghui Li; Guofeng Liu; Yang Sun; Wen Yang; Qingzhe Wang; Congcong Shen; Chao Zhang; Baoyuan Man; Jihua Wang; et al. (Chemical Engineering Journal, 2024)

Strong, anti-swelling, and biodegradable seaweed-based straws with surface mineralized CaCO3 armor - Yuanpu Liu; Wen Peng; Ting Wei; Yajie Yuan; Xianyu Cao; Meng Ma; Qingjie Sun; Man Li; Fengwei Xie (Carbohydrate Polymers, 2024)

Phytochemical and chemotaxonomic investigations on the fruit parts of Illicium verum Hook. f - Man Li; Pengcheng Yang; Mei Jin; Tieqiang Zong; Junnan Li; Sainan Li; Long Jin; Jinfeng Sun; Shengbao Diao; Wei Zhou; Gao Li (Biochemical Systematics and Ecology, 2024)

Polystyrene nanoplastics induce lipophagy via the AMPK/ULK1 pathway and block lipophagic flux leading to lipid accumulation in hepatocytes - Zhuying Fan; Yukang Zhang; Yuting Fang; Huiyuan Zhong; Tingting Wei; Huraira Akhtar; Jiahuai Zhang; Man Yang; Yanbo Li; Xianqing Zhou; Zhiwei Sun; Ji Wang (Journal of Hazardous Materials, 2024)

Efficient electrochemical nitrate reduction by iron phthalocyanine nanorods decorated on multi-walled carbon nanotubes - Wei Wang; Minzhang Li; Man Liang; Yongwang Lu; Qinyu He; Fuming Chen (Journal of Cleaner Production, 2024)

Failure Mechanism and Active Support of Large-Span Tunnel with Unstable Rock Blocks: A Case Study - Wen-xu Li; Zhi-chao Xue; Le-min Liu; Shuo Zhang; Fu-yong Zhang; Wei-teng Li; Xin-jie Man; Xing Shao; Ming-fa Wang; Chang-an Zhang (Geotechnical and Geological Engineering, 2024)

Removal of radioactive iodine by Cu2O prepared with PVP as an active agent: Role of crystal facets and oxygen vacancy in adsorption mechanisms - Xiao-Jun Dai; Kai-Wei Chen; Man-Li He; Kai Chen; Xin-Yu Zhou; Yi-Ting Chen; Chun-Hui Gong; Peng Wang; Ping Mao; Yi Yang (Chemical Engineering Journal, 2024)

Astaxanthin Rescues Memory Impairments in Rats with Vascular Dementia by Protecting Against Neuronal Death in the Hippocampus - Na Wei; Luo-man Zhang; Jing-Jing Xu; Sheng-lei Li; Rui Xue; Sheng-li Ma; Cai Li; Miao-miao Sun; Kui-sheng Chen (NeuroMolecular Medicine, 2024)

Tracing the centennial variation of East Asian Summer Monsoon - Heng Fu; Feng Shi; Wei Liu; Huihong Xue; Wenmin Man; Juan Li; Zhengtang Guo (Global and Planetary Change, 2024)

Eco-friendly drinking straws: Navigating challenges and innovations - Yuanpu Liu; Na Li; Xuyang Zhang; Ting Wei; Meng Ma; Qingjie Sun; Man Li; Fengwei Xie (Trends in Food Science & Technology, 2024)

Removal of pesticide acetamiprid using KOH activated biochar derived from crayfish shell: Behavior and mechanism - Xiao-Wen Yao; Xie Chen; Man-Li Chen; Neng-Jia Feng; Lin-Yin Tong; Yun-Qiang Yi; Wei Qian; Zeng-Hui Diao (Process Safety and Environmental Protection, 2024)

Clpf encodes pentatricopeptide repeat protein (PPR5) and regulates pink flesh color in watermelon (Citrullus lanatus L.) - Wencheng Zhang; Ziqiao Ji; Guiqiu Hu; Li Yuan; Man Liu; Xian Zhang; Chunhua Wei; Zuyun Dai; Zhongzhou Yang; Chaonan Wang; Xuezheng Wang; Feishi Luan; et al. (Theoretical and Applied Genetics, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

A novel split PEC sensor based on magneto–optic nanostructure and photocurrent polarity switching strategy - Xiang Ren; Man Wang; Jinxiu Zhao; Jinhuan Zhang; Jingui Chen; Faying Li; Qin Wei; Huangxian Ju (Analytica Chimica Acta, 2024)

Subtypes of Blastocystis in Tibetan Antelope (Pantholops hodgsonii) - Wei-Lan Yan; Xiao-Man Li; Si-Yuan Qin; Nian-Yu Xue; Yang Zou; Jing-Hao Li; Xiao-Xuan Zhang; Hong-Bo Ni (Research in Veterinary Science, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Dual-ultrasmall Sb and Sb6O13 nanodots co-anchored MXene with manipulable structural chemistry modulating bidirectional kinetics toward advanced lithium-sulfur batteries - Xinlu Zhang; Xuexiu Bai; Hengtao Shen; Zhengran Wang; Chuanliang Wei; Quanyan Man; Yuan Li; Baojuan Xi; Shenglin Xiong; Jinkui Feng (Chemical Engineering Journal, 2024)

Prediction of cytochrome P450-mediated bioactivation using machine learning models and in vitro validation - Xin-Man Hu; Yan-Yao Hou; Xin-Ru Teng; Yong Liu; Yu Li; Wei Li; Yan Li; Chun-Zhi Ai (Archives of Toxicology, 2024)

Meta-analysis of the global prevalence and risk factors of Enterocytozoon bieneusi infection in pigs from 1999 to 2021 - Xiao-Man Li; Xiang-Yu Wang; Yong-Jie Wei; Jing Jiang; Yanan Cai; Xiao-Xuan Zhang; Xing Yang; Hongwei Cao (Preventive Veterinary Medicine, 2024)

HIV encephalopathy is contributed by macrophages and microglia - Si-Meng Liu; Man Li; Chunhui Ma; Chunying Liu; An Lv; Qing Li; Yamei Niu; Peng Wang; Bo Huang; Wei-Min Tong (Science China Life Sciences, 2024)

RETRACTED: Effect of the defoliant tribufos on the reproductive ability of Japanese quail (Coturnix japonica) - Xin-Li Yan; Xue Luo; Man Xu; Ying Shi; Yi-Jin Kang; Hong-Wei Wang (Chemosphere, 2024)

Multi-phenotype response and cadmium detection of rice stem under toxic cadmium exposure - Wei Wang; Zun Man; Xiaolong Li; Yiying Zhao; Rongqin Chen; Tiantian Pan; Leiping Wang; Xiaorong Dai; Hang Xiao; Fei Liu (Science of The Total Environment, 2024)

Four uncommon cycloamphilectane-type diterpenoids with antibacterial activity from the South China Sea soft coral Sinularia brassica - Zi-Yi Xia; Man-Man Sun; Yang Jin; Ming-Zhi Su; Song-Wei Li; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

Stereoisomerically enhanced polynorbornene-imide dielectric energy storage performance - Hongmei Qin; Man Liu; Shiyu Qin; Shixian Zhang; Xingnan Zhou; Chenjian Li; Yuhao Wei; Dan Chen; Rong Fan; Shan Wang; Quanling Yang; Chuanxi Xiong; et al. (Chemical Engineering Journal, 2024)

Effect of light intensity on the accumulation of protostane triterpenes in Asian water plantain (Alisma orientale) - Wenqing Wu; Simeng Li; Wei Gu; Rong Tian; Man Luo; Junjie Tang; Min Tang; Yinzhi Wu (Acta Physiologiae Plantarum, 2024)

Tryptophan sulfonate: A new chemical marker for accurate and efficient inspection of sulfur-treated food products - Kam-Chun Chan; Wei-Hao Zhang; Yui-Man Chan; Hiu-Lam Li; Jing Fang; Han-Yan Luo; Jun Xu (Food Chemistry, 2024)

Integration of genetic engineering and multi-factor fermentation optimization for co-production of carotenoid and DHA in Schizochytrium sp - Zi-Xu Zhang; Lu-Wei Xu; Ying-Shuang Xu; Jin Li; Wang Ma; Xiao-Man Sun; He Huang (Bioresource Technology, 2024)

VX-765 Alleviates Circadian Rhythm Disorder in a Rodent Model of Traumatic Brain Injury Plus Hemorrhagic Shock and Resuscitation - Yan Li; Yue Xin; Man-Man Qi; Zhi-You Wu; Han Wang; Wei-Chao Zheng; Jie-Xia Wang; Dong-Xue Zhang; Li-Min Zhang (Journal of Neuroimmune Pharmacology, 2024)

Corrigendum to “Oral self-microemulsifying drug delivery system for honokiol's stress responses attenuation and anti-Cryptocaryon irritans efficacy enhancement in Trachinotus ovatus” [Aquaculture 578(15): 740130, 2024] - Yong-Can Zhou; Gui-Hua Li; Shao-Long Liu; Man-Yi Jiang; Zi-Chen Zhao; Heng-Wei Deng; Jian-Long Li; Dong-Dong Zhang; Wei-Liang Guo; Ji-Hui Huang (Aquaculture, 2024)

Oral self-microemulsifying drug delivery system for honokiol's stress responses attenuation and anti-Cryptocaryon irritans efficacy enhancement in Trachinotus ovatus - Yong-Can Zhou; Gui-Hua Li; Shao-Long Liu; Man-Yi Jiang; Zi-Chen Zhao; Heng-Wei Deng; Jian-Long Li; Dong-Dong Zhang; Wei-Liang Guo; Ji-Hui Huang (Aquaculture, 2024)

Impact of mineral dust photocatalytic heterogeneous chemistry on the formation of the sulfate and nitrate: A modelling study over East Asia - Xiao Li; Zechen Yu; Man Yue; Yaman Liu; Kan Huang; Xuguang Chi; Wei Nie; Aijun Ding; Xinyi Dong; Minghuai Wang (Atmospheric Environment, 2024)

Microwave-assisted one-pot preparation of magnetic cactus-derived hydrochar for efficient removal of lead(Ⅱ) and phenol from water: Performance and mechanism exploration - Jianhua Qu; Zhaolin Du; Yue Lei; Man Li; Wei Peng; Mengning Wang; Jie Liu; Qi Hu; Lei Wang; Yifan Wang; Ying Zhang (Bioresource Technology, 2023)

Efficient genome editing in cotton using the virus-mediated CRISPR/Cas9 and grafting system - Wei-Feng Guo; Dan-Dan Guo; Fen Li; Shen-Zhai Shang; Ting-Wan Li; Ying-Chao Tang; Man Jiang; Fu-Chun Xu; Wei Gao (Plant Cell Reports, 2023)

Efficient activation of persulfate by metallic sulfide mineral for the efficient removal of pesticides: Performance, radical generation and mechanism - Xie Chen; Wen-Xuan Zhang; Zhi-Liang Chen; Xiao-Wen Yao; Man-Li Chen; Lin-Yin Tong; Wei Qian; Peng-Ran Guo; Ling-Jun Kong; Zeng-Hui Diao (Journal of Cleaner Production, 2023)

Kinetics study on the catalytic recombination of non-premixed hydrogen–oxygen system: Effects of initial temperature, oxygen flow rate, and hydrogen diffusion time - Xuan Li; Si-Yuan Zhou; Jing Zhang; Zhuo-Wei Guo; Man-Qi Guan; Bin Li; Dan Zhang; Yong-Xu Wang; Li-Feng Xie (Fuel, 2023)

Tree roots exert greater impacts on phosphorus fractions than aboveground litter in mineral soils under a Pinus sylvestris var. mongolica plantation - Xiang Zhang; Qiong Zhao; Li-Man Wei; Qing-Ye Sun; De-Hui Zeng (Forest Ecology and Management, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

Simultaneous detection of multiple influenza virus subtypes based on microbead-encoded microfluidic chip - Shao-Li Hong; Xuan Wang; Zhong-Hua Bao; Meng-Fan Zhang; Man Tang; Nangang Zhang; Huihong Liu; Zi-Yuan Zhu; Kan Liu; Zhi-Liang Chen; Wei Li (Analytica Chimica Acta, 2023)

Correction to: Silica nanoparticle exposure inducing granulosa cell apoptosis and follicular atresia in female Balb/c mice - Jianhui Liu; Man Yang; Li Jing; Lihua Ren; Jialiu Wei; Jin Zhang; Feng Zhang; Junchao Duan; Xianqing Zhou; Zhiwei Sun (Environmental Science and Pollution Research, 2023)

Square ancient sites detection in typical regions of the Mongolian plateau using improved faster R-CNN from Google Earth high-resolution images - Wei Li; Zhe Li; Yongfeng Wei; Caili Gong; Man Zhang; Liang Chen (International Journal of Remote Sensing, 2023)

Sources, size-resolved deposition in the human respiratory tract and health risks of submicron black carbon in urban atmosphere in Pearl River Delta, China - Yuan Liu; Lina Wu; Shan Huang; Qicong Song; Weiwei Hu; Wei Chen; Zhijun Wu; Ruiqi Man; Yao He; Wei Li; Yuwen Peng; Junwen Liu; et al. (Science of The Total Environment, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Quercetin prevents the ferroptosis of OPCs by inhibiting the Id2/transferrin pathway - Yeyang Wang; Wenjun Li; Mingsen Wang; Hongdong Chen; Yongsheng Li; Wei Wei; Xuhua Liu; Yuelin Wu; Sidong Luo; Xinfang Liu; Man Xiong (Chemico-Biological Interactions, 2023)

Two new isoquinolines from Corydalis saxicola - Zhi-Wei Ouyang; Ji-Man He; Feng Qin; Ling Li; Wen-Di Tang; Dian-Peng Li; Jiang-Ke Qin (Natural Product Research, 2023)

Rainstorm events trigger algal blooms in a large oligotrophic reservoir - Pengcheng Shi; Mengyuan Zhu; Rifu You; Huiyun Li; Wei Zou; Hai Xu; Man Xiao; Guangwei Zhu (Journal of Hydrology, 2023)

Meta-analysis reveals cyanotoxins risk across African inland waters - Xu Zhao; Ying Liu; Yu-Ming Guo; Chi Xu; Liang Chen; Geoffrey A. Codd; Jun Chen; Ying Wang; Pu-Ze Wang; Li-Wei Yang; Long Zhou; Yan Li; et al. (Journal of Hazardous Materials, 2023)

Investigation of nuclide migration in complex fractures with filling properties - Guowei Ma; Yun Chen; Wei Dong; Man Xu; Tuo Li; Huidong Wang (Journal of Cleaner Production, 2023)

A portable holey carbon nitride/3D Ag facilely self-assembled on copper sheet for dramatically enhanced SERS and photocatalytic performance - Lixia Qin; Min Tang; Hui Shen; Man Luo; Jian-Wei Tao; Taiyang Zhang; Shi-Zhao Kang; Xiangqing Li (Chemical Engineering Journal, 2023)

Response mechanism and rapid detection of phenotypic information in rice root under heavy metal stress - Wei Wang; Zun Man; Xiaolong Li; Rongqin Chen; Zhengkai You; Tiantian Pan; Xiaorong Dai; Hang Xiao; Fei Liu (Journal of Hazardous Materials, 2023)

Geochemical processes and indicative significance of rare earth elements in high arsenic geothermal fluids in Batang, western Sichuan, China - wei Zhang; hanxiong Zhang; guiling Wang; jiayi Zhao; gaofan Yue; man Li; shuaichao Wei; zewei Qu (Geothermics, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Electronic and structural engineering of supported single atomic layer, low-nuclearity palladium catalysts for conversion of levulinic acid to 1,4-pentanediol - Xiaowen Lu; Tingting Luo; Mingyang Zhang; J Hugh Horton; Qiong Wu; Wei Wu; Man Qiao; Yu Wang; Zhijun Li (Chemical Engineering Journal, 2023)

Methods and experiments for collecting information and constructing models of bottom-layer contours in paddy fields - Tuanpeng Tu; Jie He; Xiwen Luo; Lian Hu; Pei Wang; Gaolong Chen; Li Tian; Dawen Feng; Zhimin Wang; Zhongxian Man; Weicong Li; Zhenghui Wei; et al. (Computers and Electronics in Agriculture, 2023)

Periploca sepium leaf dry weight, area, and thickness scale differently under different light environments in Taohe riparian forests - Min Ma; Cheng-Zhang Zhao; Man-Ping Kang; Xiao-Ya Li; Zhi-Wei Zhang; Xu-Qian Bai (Flora, 2023)

Asymmetric coordinated single-atom Pd sites for high performance CO2 electroreduction and Zn–CO2 battery - Jiani Li; Li-Wei Chen; Yu-Chen Hao; Man Yuan; Jianning Lv; Anwang Dong; Shuai Li; Hongfei Gu; An-Xiang Yin; Wenxing Chen; Pengfei Li; Bo Wang (Chemical Engineering Journal, 2023)

Anisotropic creep behavior of soft-hard interbedded rock masses based on 3D printing and digital imaging correlation technology - Yun Tian; Fa-quan Wu; Hong-ming Tian; Zhe Li; Xiao-yun Shu; Lin-kai He; Man Huang; Wei-zhong Chen (Journal of Mountain Science, 2023)

Ultrasensitive fluorescence detection of multiple DNA methyltransferases based on DNA walkers and hyperbranched rolling circle amplification - Siqi Zhang; Huahao Shao; Kai-Bin Li; Wei Shi; Yichao Wang; De-Man Han; Jinggang Mo (Analytica Chimica Acta, 2023)

Differential characteristics of carbon emission efficiency and coordinated emission reduction pathways under different stages of economic development: Evidence from the Yangtze River Delta, China - Chonggang Liu; Wei Sun; Pingxing Li; Luocheng Zhang; Man Li (Journal of Environmental Management, 2023)

Differences in texture and digestive properties of different parts in boiled abalone muscles - Man-Man Yu; Ying-Chen Fan; De-Yang Li; Yu-Xin Liu; Peng-Fei Jiang; Da-Yong Zhou; Bei-Wei Zhu (Food Chemistry, 2023)

Microcystin-LR exposure interfered maintenance of colonic microenvironmental homeostasis in rat - Yang Liu; Chun-Li Qi; Da-Wei Li; Hong-Ye Li; Rui-Man Li; Wei-Dong Yang (Food and Chemical Toxicology, 2023)

Electrophysiological microenvironment and site-specific cell behaviors regulated by fibrous aniline trimer-based polyurethanes in bone progressive regeneration - Jiajing Tang; Yinglong Zhang; Wei Fang; Yi Man; Jinzheng Zhang; Qing Zhao; Xiaoyu Lei; Jieqiong Chen; Jidong Li; Yubao Li; Yi Zuo (Chemical Engineering Journal, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Curbing per- and polyfluoroalkyl substances (PFASs): First investigation in a constructed wetland-microbial fuel cell system - Bin Ji; Yaqian Zhao; Yang Yang; Qiwen Li; Ying Man; Yunv Dai; Jingmiao Fu; Ting Wei; Yiping Tai; Xiaomeng Zhang (Water Research, 2023)

Nitrogen-doped Ti3C2Tx MXene prepared by thermal decomposition of ammonium salts and its application in flexible quasi-solid-state supercapacitor - Man Cai; Xiaochun Wei; Haifu Huang; Fulin Yuan; Cong Li; Shuaikai Xu; Xianqing Liang; Wenzheng Zhou; Jin Guo (Chemical Engineering Journal, 2023)

Reduction of gross N Transformations to Moisture Changes in a Wetland Ecosystem: The Case of Marshland Conversion to Cropland - Ping Li; Man Lang; Wei Wei; Sixi Zhu (Wetlands, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Optimizing simulation of summer precipitation by weather research and forecasting model over the mountainous southern Tibetan Plateau - Huancai Liu; Xuna Zhao; Keqin Duan; Wei Shang; Man Li; Peihong Shi (Atmospheric Research, 2023)

5′-Nucleotidase is dispensable for the growth of Salmonella Typhimurium but inhibits the bactericidal activity of macrophage extracellular traps - Man Qian; Ke Xu; Mengke Zhang; Junhui Niu; Tianxiang Zhao; Xiaoli Wang; Yanyan Jia; Jing Li; Zuhua Yu; Lei He; Yinju Li; Tingcai Wu; et al. (Archives of Microbiology, 2023)

Aaptamine derivatives with CDK2 inhibitory activities from the South China Sea sponge Aaptos suberitoides - Qian-Qian He; Yu-Qing Man; Kun-Lai Sun; Li-Juan Yang; Yan Wu; Jing Du; Wei-Wei Chen; Juan-Juan Dai; Na Ni; Shuang Miao; Kai-Kai Gong (Natural Product Research, 2022)

The Super-large Ensemble Experiments of CAS FGOALS-g3 - Pengfei Lin; Bowen Zhao; Jilin Wei; Hailong Liu; Wenxia Zhang; Xiaolong Chen; Jie Jiang; Mengrong Ding; Wenmin Man; Jinrong Jiang; Xu Zhang; Yuewen Ding; et al. (Advances in Atmospheric Sciences, 2022)
A super-large ensemble simulation dataset with 110 members has been produced by the fully coupled model FGOALS-g3 developed by researchers at the Institute of Atmospheric Physics, Chinese Academy of Sciences. This is the first dataset of large ensemble simulations with a climate system model developed by a Chinese modeling center. The simulation has the largest realizations up to now worldwide in terms of single-model initial-condition large ensembles. Each member includes a historical experiment (1850–2014) and an experiment (2015–99) under the very high greenhouse gas emissions Shared Socioeconomic Pathway scenario (SSP5-8.5). The dataset includes monthly and daily temperature, precipitation, and other variables, requiring storage of 275 TB. Additionally, the surface air temperature (SAT) and land precipitation simulated by the FGOALS-g3 super-large ensemble have been validated and projected. The ensemble can capture the response of SAT and land precipitation to external forcings well, and the internal variabilities can be quantified. The availability of more than 100 realizations will help researchers to study rare events and improve the understanding of the impact of internal variability on forced climate changes.

Exploring the R-ISS stage-specific regular networks in the progression of multiple myeloma at single-cell resolution - Ling Zhong; Xiao Yang; Yu Zhou; Jialing Xiao; Huan Li; Jiang Tao; Qian Xi; Chen Chu; Chenglong Li; Xi Yang; Chen Yang; Yi Zhang; et al. (Science China Life Sciences, 2022)

Dyadobacter diqingensis sp. nov., isolated from Baima snow mountain of Diqing Tibetan Autonomous Prefecture in Yunnan province, south-west China - Lei Ran; Man Peng; Wei-Qun Wang; Yu-Zhou Feng; Juan Wang; Yu Wang; Cui-Ying Li; Xin-Xing Liu; Wei-Xun Chunyu; Shu-Kun Tang (Archives of Microbiology, 2022)

Analysis of gene expression changes in wheat in response to Rhizoctonia cerealis infection using RNA-Seq - Xujiang Wu; Junchan Wang; Lei Li; Xiao Zhang; Wei Jiang; Man Li; Derong Gao; Boqiao Zhang; Chengbin Lu (Journal of Plant Pathology, 2022)
Bread wheat ( Triticum aestivum L.) is the most widely grown crop in the world. Rhizoctonia cerealis , the causal agent of wheat sharp eyespot disease, has 21 become epidemic in many countries. In the present study, we performed transcriptome analysis in wheat infected by R. cerealis at 0, 12, 30, 70, and 98 h post-infection using R. cerealis -resistant and -susceptible genotypes (CI12633 and ‘Yangmai15’, respectively). We used quantitative real-time PCR to validate the Illumina gene expression data, and identified new gene annotations for 23,654 unigenes in the RNA samples from the resistant and susceptible cultivars. Comparing the same inoculation times, we found that the number of DEGs (differentially-expressed genes) increased gradually before 70 h and declined at 98 h in the two RNA samples. Furthermore, the expression of resistance-associated genes occurred earlier in CI12633 than in ‘Yangmai15’, and higher mRNA expression levels were detected in CI12633; this suggests that timing and relative expression levels of these genes are important in the CI12633- R. cerealis interaction. Functional annotations associated with sharp eyespot resistance included genes involved in energy production and conversion, posttranslational modification, protein turnover, chaperones, secondary metabolite biosynthesis, transport and catabolism, and defense mechanisms. The results of pathway enrichment analysis showed that the DEGs participate in glutathione metabolism, glycerophospholipid metabolism, lysine degradation, plant-pathogen interaction, glyoxylate and dicarboxylate metabolism, and other resistance-associated metabolic pathways. Disease inoculation experiments and the validation of in vitro antifungal activity of the candidate genes showed that the genes were up- or down-regulated in the resistant genotype CI12633 30 h after inoculation compared to its control, which validated the results of the RNA-seq analysis. The results of our study will help to understand the molecular basis of the host response to R. cerealis infection in wheat, and will also enable the future genetic improvement of sharp eyespot resistance in wheat through the incorporation of novel resistance genes.

The Effects of Long-Term High Water Iodine Levels in the External Environment on the Carotid Artery - Ji Bian; Man Zhang; Feng Li; Jie Gao; Zhexue Wei; Zijing Liu; Xiaoming Wang; Wen Jiang; Jianchao Bian (Biological Trace Element Research, 2022)
Iodine excess typically affects thyroid function in the human body and may damage carotid artery. Four investigation plots with different water iodine levels were selected in Shandong Province, China. These included a low, medium, and high iodine group and an iodine excess group whose water iodine content was < 10, 50–150, 150–300, and > 300 μg/L, respectively. Residents aged 20–65 years answered a questionnaire and underwent carotid artery ultrasonography, and their height, weight, and urinary iodine concentrations were measured. A total of 2026 individuals participated in the study. Urinary iodine concentration increased with increased water iodine levels. The medial thickening rate and intimal roughness rate in the iodine excess group were significantly higher than in the other three groups. After controlling for factors such as gender, age, and BMI, iodine excess remained as a risk factor for carotid intima-media thickening. Excess water iodine in the external environment is a risk factor for intima-media thickening of the carotid artery, suggesting that iodine excess may cause vascular injury and promote atherosclerosis.

Potential Application of Biosurfactant-Producing Bacteria for Bioremediation of Oil Polluted Marine Intertidal Sediments - Ping Guo; Wei-Wei Xu; Dan-Na Wei; Man-Xia Zhang; Jin Zhang; Shi Tang; Bin-Xia Cao; Jian-Guo Lin; Wei Li (Journal of Marine Science and Engineering, 2022)
The removal of oil contaminants in marine intertidal sediments under cold climate is an urgent issue. Although the bioavailability of petroleum hydrocarbons decreases at low temperatures, biosurfactants can promote oil biodegradation. In this study, characteristics of biosurfactants produced by cold-adapted oil-degrading bacteria Planococcus sp. XW-1 were studied. Adding the XW-1 biosurfactant could effectively facilitate the solubility of phenanthrene, pyrene, diesel oil, and crude oil. The solubilization was limited by the number of rings and the molecular weight (WSRphenanthrene = 0.0234; WSRpyrene = 0.0165; WSRdiesel oil = 0.0027; WSRcrude oil = 0.0015). Additional biosurfactants significantly washed out crude oil adsorbed to the sand (reduction from 17.1%, 22.7% to 87.9% and 94.28% in 24 h). With the increase in particle size, the removal efficiency increased from 87.9% to 94.28%. After the addition of biosurfactant, the effect of degradation increased by 20% in 20 days. The results suggest that the biosurfactant-producing bacteria Planococcus sp. XW-1 is a promising candidate used in the in situ bioremediation of petroleum-contaminated intertidal sediment.

3D Seismic Stability Analysis of Bench Slope with Pile Reinforcement - Sheng-yu Yang; Zhen Wang; Jia-man Wang; Ming-wei Gong; Jian-fei Li; Zhi-bin Sun (Geotechnical and Geological Engineering, 2022)

Land development suitability analysis for transport planning evaluation and optimization in mountainous ecological region - Gao-ru Zhu; Man Wang; Qi-li Li; Jie Liu; Yan-ni Zhao; Jia-wei Gao; Hong-lei Xu (Journal of Mountain Science, 2022)

Caldalkalibacillus salinus sp. nov., isolated from a salt lake in Xinjiang, northwest China - Ting-Hao Ouyang; Man Peng; Zhen Zhang; Wei-Xun Chunyu; Li-Ming Wang; En-Min Zhou; Xu-Hong Gao; Shu-Kun Tang (Archives of Microbiology, 2022)

Dysfunction of FadA‐cAMP signalling decreases Aspergillus flavus resistance to antimicrobial natural preservative Perillaldehyde and AFB1 biosynthesis - Kunlong Yang; Qingru Geng; Yue Luo; Rui Xie; Tongzheng Sun; Zhen Wang; Ling Qin; Wei Zhao; Man Liu; Yongxin Li; Jun Tian (Environmental Microbiology, 2022)
Summary Aspergillus flavus is an opportunistic fungal pathogen that colonizes agriculture crops with aflatoxin contamination. We found that Perillaldehyde (PAE) effectively inhibited A . flavus viability and aflatoxin production by inducing excess reactive oxygen species (ROS). Transcriptome analysis indicated that the Gα protein FadA was significantly induced by PAE. Functional characterization of FadA showed it is important for asexual development and aflatoxin biosynthesis by regulation of cAMP‐PKA signalling. The Δ fadA mutant was more sensitive to PAE, while Δ pdeL and Δ pdeH mutants can tolerate excess PAE compared to wild‐type A . flavus . Further RNA‐sequence analysis showed that fadA was important for expression of genes involved in oxidation–reduction and cellular metabolism. The flow cytometry and fluorescence microscopy demonstrated that Δ fadA accumulated more concentration of ROS in cells, and the transcriptome data indicated that genes involved in ROS scavenging were downregulated in Δ fadA mutant. We further found that FadA participated in regulating response to extracellular environmental stresses by increasing phosphorylation levels of MAPK Kinase Slt2 and Hog1. Overall, our results indicated that FadA signalling engages in mycotoxin production and A . flavus resistance to antimicrobial PAE, which provide valuable information for controlling this fungus and AF biosynthesis in pre‐ and postharvest of agricultural crops.

Characteristics and formation mechanism of siltstone-mudstone rhythmic sedimentary sections in the Lower Silurian Longmaxi Formation in the Changning area, South Sichuan Basin, southwest China - Gaoxiang Wang; Lei Chen; Yang Yang; Cui Jing; Man Chen; Xiucheng Tan; Xin Chen; Di Cao; Zibo Wei; Minglong Li; Dong Huang (Frontiers of Earth Science, 2021)

Three new dimeric 2-(2-phenylethyl)chromones from artificial agarwood of Aquilaria sinensis - Pan Xiang; Wen-Hua Dong; Cai-Hong Cai; Wei Li; Li-Man Zhou; Hao-Fu Dai; Hui-Qin Chen; Wen-Li Mei (Natural Product Research, 2021)

Global patterns in leaf stoichiometry across coastal wetlands - Yu‐Kun Hu; Xu‐Yan Liu; Nian‐Peng He; Xu Pan; Song‐Yuan Long; Wei Li; Man‐Yin Zhang; Li‐Juan Cui (Global Ecology and Biogeography, 2021)
Aim Coastal wetlands provide crucial ecosystem functions and services, such as coastal protection, nutrient retention and C sequestration. Despite the important roles in global C, N and P cycling, the global variation in leaf stoichiometry across coastal wetlands remains unclear. Location Global. Time period 1980–2018. Major taxa studied Vascular plants. Methods By compiling a global dataset of 698 data records in 205 sites, we carried out systematic analyses of the world‐wide trends and their determinants of leaf element contents and ratios of plants across coastal wetlands. Results Leaf N and P contents increased significantly, but C:N, C:P and N:P ratios decreased with increasing latitude in coastal wetlands. The mean annual temperature was the predominant driver of leaf N, P and C:N, whereas soil N:P was a good predictor of leaf C:P and N:P ratios. Furthermore, N increased faster with P in plant leaves of coastal wetlands compared with terrestrial ecosystems. Within coastal wetlands, herb‐dominated salt marshes had a significantly higher leaf P content, lower leaf N:P ratio and lower scaling exponent of leaf N to P than tree‐dominated mangroves. Main conclusions The similar latitudinal patterns of leaf stoichiometry in coastal wetlands compared with terrestrial ecosystems reflected the similar influences of temperature. However, different slopes of leaf P and N:P ratios and N and P scaling relationships between these two ecosystems suggested that different salinity and tidal inundation levels result in different strategies of N and P use in coastal wetland plants. These differences in leaf stoichiometry between ecosystems and between different types of coastal wetlands might need to be emphasized in future biogeochemical modelling owing to their different roles in global nutrient and carbon cycling.

Evaluating pluvial flood hazard for highly urbanised cities: a case study of the Pearl River Delta Region in China - Wei Jian; Shanshan Li; Chengguang Lai; Zhaoli Wang; Xiangju Cheng; Edmond Yat-Man Lo; Tso-Chien Pan (Natural Hazards, 2021)

Bioactive triterpenoids from Sambucus javanica Blume - Feilong Chen; Dong-Li Liu; Wei Wang; Xiao-Man Lv; Weixi Li; Li-Dong Shao; Wen-Jing Wang (Natural Product Research, 2020)

Discrimination of mine water-inflow sources based on the multivariate mixed model and fuzzy comprehensive evaluation - Jiuchuan Wei; Guanghui Li; Daolei Xie; Gongyishan Yu; Xiaoquan Man; Jie Wang (Arabian Journal of Geosciences, 2020)

Baicalein attenuates caspase-independent cells death via inhibiting PARP-1 activation and AIF nuclear translocation in cerebral ischemia/reperfusion rats - Wei-Han Li; Ying-Lin Yang; Xiao Cheng; Man Liu; Shan-Shan Zhang; Yue-Hua Wang; Guan-Hua Du (Apoptosis, 2020)

Chemical constituents from the deep sea-derived Streptomyces xiamenensis MCCC 1A01570 and their effects on RXRα transcriptional regulation - Wei-Xiang Lin; Chun-Lan Xie; Mi Zhou; Man-Li Xia; Ting-Ting Zhou; Hai-Feng Chen; Xian-Wen Yang; Quan Yang (Natural Product Research, 2020)

Dialectical behavior therapy-based psychological intervention for woman in late pregnancy and early postpartum suffering from COVID-19: a case report - Jin-wen Huang; Xiao-yi Zhou; Shao-jia Lu; Yi Xu; Jian-bo Hu; Man-li Huang; Hua-fen Wang; Chan-chan Hu; Shu-guang Li; Jing-kai Chen; Zhong Wang; Shao-hua Hu; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Dynamic Alterations of Brain Injury, Functional Recovery, and Metabolites Profile after Cerebral Ischemia/Reperfusion in Rats Contributes to Potential Biomarkers - Xiao Cheng; Ying-Lin Yang; Wei-Han Li; Man Liu; Shan-Shan Zhang; Yue-Hua Wang; Guan-Hua Du (Journal of Molecular Neuroscience, 2020)

Tunneling nanotubes mediate intercellular communication between endothelial progenitor cells and osteoclast precursors - Rui-Fang Li; Wei Zhang; Qi-Wen Man; Yi-Fang Zhao; Yi Zhao (Journal of Molecular Histology, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Contrasting Soil Bacterial and Fungal Communities between the Swamp and Upland in the Boreal Forest and their Biogeographic Distribution Patterns - Jing Li; Hang-Wei Hu; Zhang-Jie Cai; Yin-Ru Lei; Man-Yin Zhang; Wei Li; Jun-Tao Wang (Wetlands, 2019)

Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2019)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

The complete mitochondrial genome of Pseudocrossocheilus bamaensis (Cypriniformes: Cyprinidae: Labeoninae) - Man Zhang; Bo-wen Liu; Guang-ping Cheng; Li Bian; Qi-jia Zhou; Wei-jie Yan; Wen-hong Li (Conservation Genetics Resources, 2018)

Deletion of Type-2 Cannabinoid Receptor Induces Alzheimer’s Disease-Like Tau Pathology and Memory Impairment Through AMPK/GSK3β Pathway - Lin Wang; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Dong-Sheng Sun; Meng-Zhu Li; Fang-Xiao Shi; Man Li; Qing Tian; Jian-Zhi Wang; Xin-Wen Zhou (Molecular Neurobiology, 2018)

Integrated analysis of transcriptomic and metabolomic data reveals critical metabolic pathways involved in rotenoid biosynthesis in the medicinal plant Mirabilis himalaica - Li Gu; Zhong-yi Zhang; Hong Quan; Ming-jie Li; Fang-yu Zhao; Yuan-jiang Xu; Jiang Liu; Man Sai; Wei-lie Zheng; Xiao-zhong Lan (Molecular Genetics and Genomics, 2018)

Two new phenolic constituents from the root bark of Morus alba L. and their cardioprotective activity - Yan-gang Cao; Xiao-ke Zheng; Fang-fang Yang; Fang Li; Man Qi; Yan-li Zhang; Xuan Zhao; Hai-xue Kuang; Wei-sheng Feng (Natural Product Research, 2018)

Silica nanoparticle exposure inducing granulosa cell apoptosis and follicular atresia in female Balb/c mice - Jianhui Liu; Man Yang; Li Jing; Lihua Ren; Jialiu Wei; Jin Zhang; Feng Zhang; Junchao Duan; Xianqing Zhou; Zhiwei Sun (Environmental Science and Pollution Research, 2018)

mPGES-1-derived prostaglandin E2 stimulates Stat3 to promote podocyte apoptosis - Jing Yu; Yimei Wu; Lu Wang; Wen Zhang; Man Xu; Jiayu Song; Yu Fu; Yiyun Cui; Wei Gong; Shuzhen Li; Weiwei Xia; Songming Huang; et al. (Apoptosis, 2017)

Landscape dynamics and driving forces of wetlands in the Tumen River Basin of China over the past 50 years - Xiao Jun Zheng; Peng Sun; Wei Hong Zhu; Zhen Xu; Jing Fu; Wei Dong Man; Hai Long Li; Jian Zhang; Lei Qin (Landscape and Ecological Engineering, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

Overexpression of a heading Chinese cabbage ICE1 gene confers freezing tolerance in transgenic rice - Dianjun Xiang; Yongshan Chai; Lili Man; Yuyou Sun; Taizhong Zhang; Caiqiang Wei; Zhong Xie; Hongliang Li; Weiwei Zhang; Dan Liu; Dujuan Cheng; Xiaodong Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Endosulfan inducing apoptosis and necroptosis through activation RIPK signaling pathway in human umbilical vascular endothelial cells - Lianshuang Zhang; Jialiu Wei; Lihua Ren; Jin Zhang; Man Yang; Li Jing; Ji Wang; Zhiwei Sun; Xianqing Zhou (Environmental Science and Pollution Research, 2017)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

Over-Expression of PmHSP17.9 in Transgenic Arabidopsis thaliana Confers Thermotolerance - Xue-Li Wan; Jie Yang; Xiao-Bai Li; Qiao Zhou; Cong Guo; Man-Zhu Bao; Jun-Wei Zhang (Plant Molecular Biology Reporter, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Endosulfan inhibiting the meiosis process via depressing expressions of regulatory factors and causing cell cycle arrest in spermatogenic cells - Fang-Zi Guo; Lian-Shuang Zhang; Jia-Liu Wei; Li-Hua Ren; Jin Zhang; Li Jing; Man Yang; Ji Wang; Zhi-Wei Sun; Xian-Qing Zhou (Environmental Science and Pollution Research, 2016)

Interspecific variation in extracellular polysaccharide content and colony formation of Microcystis spp. cultured under different light intensities and temperatures - Feng Xu; Wei Zhu; Man Xiao; Ming Li (Journal of Applied Phycology, 2016)

Hydrochemical characteristics and quality assessment of deep groundwater from the coal-bearing aquifer of the Linhuan coal-mining district, Northern Anhui Province, China - Man-li Lin; Wei-hua Peng; He-rong Gui (Environmental Monitoring and Assessment, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

Genome characterization and phylogenetic analysis of a lineage IV peste des petits ruminants virus in southern China - Xiao-Peng Li; Shao-Lun Zhai; Dong-Sheng He; Peng-Ju Guo; Dian-Hong Lv; Xiao-Hui Wen; Man-Lin Luo; Rui-Ai Chen; Wen-Kang Wei (Virus Genes, 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

In vivo expression patterns of microRNAs of Gallid herpesvirus 2 (GaHV-2) during the virus life cycle and development of Marek’s disease lymphomas - Pu Zhao; Xiu-Jie Li; Man Teng; Lu Dang; Zu-Hua Yu; Jia-Qi Chi; Jing-Wei Su; Gai-Ping Zhang; Jun Luo (Virus Genes, 2015)

Size-dependent growth of Microcystis colonies in a shallow, hypertrophic lake: use of the RNA-to-total organic carbon ratio - Ming Li; Wei Zhu; Xiaoxuan Dai; Man Xiao; Gloria Appiah-Sefah; Philip Nti Nkrumah (Aquatic Ecology, 2014)

Atorvastatin inhibits hyperglycemia-induced expression of osteopontin in the diabetic rat kidney via the p38 MAPK pathway - Li Zuo; Yong Du; Man Lu; Junling Gao; Ruolei Hu; Sumei Zhang; Yi Wang; Huaqing Zhu; Qing Zhou; Wei Wei; Yuan Wang (Molecular Biology Reports, 2014)

Regulation of Involucrin in Psoriatic Epidermal Keratinocytes: The Roles of ERK1/2 and GSK-3β - Jia-Qi Chen; Xiao-Yong Man; Wei Li; Jiong Zhou; Lilla Landeck; Sui-Qing Cai; Min Zheng (Cell Biochemistry and Biophysics, 2013)

Acid loading stimulates rat glomerular mesangial cells proliferation through Na+–H+ exchanger isoform 1 (NHE1)-dependent pathway - Kun Li; Wei Su; Man Li; Chang-jie Chen; Yong-yu Li; Lin-yun Lai; Ming-min Zhang; Shao-jun Liu; Jakub Fichna; Ai Peng; Chuan-ming Hao; Yong Gu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Roles of Wnt/β-Catenin Signaling in Retinal Neuron-Like Differentiation of Bone Marrow Mesenchymal Stem Cells from Nonobese Diabetic Mice - Yue Xu; Zhifeng Gu; Biyu Shen; Guofeng Xu; Tianqiu Zhou; Jinxia Jiang; Jing Xing; Suzhe Liu; Man Li; Wei Tan; Guijuan Feng; Aimin Sang; et al. (Journal of Molecular Neuroscience, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

Efficacy of endosulfan and fipronil and joint toxic action of endosulfan mixtures against Leptinotarsa decemlineata (Say) - Xiao-qin Shi; Man-Hui Xiong; Wei-Hua Jiang; Zhi-Tian Wang; Wen-Chao Guo; Zhen-Han Xia; Wen-Jun Fu; Guo-Qing Li (Journal of Pest Science, 2012)

Virgibacillus albus sp. nov., a novel moderately halophilic bacterium isolated from Lop Nur salt lake in Xinjiang province, China - Yun-Jiao Zhang; Yu Zhou; Man Ja; Rong Shi; Wei-Xun Chun-Yu; Ling-Ling Yang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Widespread expression of zinc transporter ZnT (SLC30) family members in mouse endocrine cells - Man-Li Zhong; Zhi-Hong Chi; Zhong-Yan Shan; Wei-Ping Teng; Zhan-You Wang (Histochemistry and Cell Biology, 2012)

VEGF upregulates VEGF receptor-2 on human outer root sheath cells and stimulates proliferation through ERK pathway - Wei Li; Zhong-Fa Lu; Xiao-Yong Man; Chun-Ming Li; Jiong Zhou; Jia-Qi Chen; Xiao-Hong Yang; Xian-Jie Wu; Sui-Qing Cai; Min Zheng (Molecular Biology Reports, 2012)

Pigment epithelium-derived factor plays an inhibitory role in proliferation and migration of HaCaT cells - Chun-Ming Li; Wei Li; Xiao-Yong Man; Jiong Zhou; Jia-Qi Chen; Sui-Qing Cai; Min Zheng (Molecular Biology Reports, 2011)

Regulation of adhesion by vascular endothelial growth factor in HaCaT cells - ChunMing Li; XiaoYong Man; Wei Li; Jiong Zhou; JiaQi Chen; SuiQing Cai; Min Zheng (Molecular and Cellular Biochemistry, 2011)

Cloning and Characterization of the Promoter of the Human AHI1 Gene - Xian-Fang Meng; Yi Luo; Wei Xiao; Man Li; Jing Shi (Biochemical Genetics, 2009)

Identification ofporphyra lines (rhodophyta) by AFLP DNA fingerprinting and molecular markers - Jian Wei Sun; Min De Jin; Chun Jiang Zhou; Qing Kai Yang; Man Li Weng; Lin De Duan; Pu Xu; Jia Hai Ma; Bin Wang (Plant Molecular Biology Reporter, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)